The Republic public prosecutor: Between the law and politics - what prevails? - Krstić Gordana (Zbornik Radova Pravnog Fakulteta u Nišu, 2019)
This paper analizes the position of the Republic Public Prosecutor in normative and practical terms, with special reference to his/her appointment, authority and responsibility. Given the fact that the Republic Public Prosecutor is elected by the National Assembly among the candidates who are suggested by the Government, political influence definitively exists, but it is important to set boundaries to political impact and to ensure the application of the law in individual cases. After the appointment, the Republic Public Prosecutor should be independent; he/she is required to establish the criminal prosecution strategy which will define the types of crimes which should be suppressed by lower-ranking prosecutors during his/her mandate. The paper also elaborates on the functions of the Republic Public Prosecutor, who has the exclusive right to initiate the extraordinary review proceedings, not only in criminal matters but also in civil and administrative proceedings. According to the Criminal Procedure Code, the Republic Public Prosecutor decides on the objection of the injured party which is submitted against the decision of the prosecutor of special jurisdiction, in case he/she dismisses the complaint, discontinues the investigation or abandons criminal prosecution. The Republic Public Prosecutor has a competence to order controlled delivery proceedings as a special evidentiary action aimed at collecting evidence for instituting criminal proceedings and detecting suspects. As the highest general prosecutor who is at the forefront of the entire organization of the prosecutor's office, the Republic Public Prosecutor has organizational and supervisory functions which are connected to the decisions and activities of other subordinate prosecutors. He/she gives mandatory instructions to the lower-ranking prosecutors and finally decides on legal remedies against the mandatory instructions when a subordinate prosecutor finds the instruction incompatible with the law or his/her legal conviction. The power to give instructions to a subordinate prosecutor does not only refer to general instructions but also extends to the manner of acting in particular cases, but this provision should be differently regulated by the law. The Republic Public Prosecutor can also take cases from a subordinate prosecutor or assign them to other subordinate prosecutors. He/She is also entitled to issue written general orders, resolutions and instructions that guarantee legality, efficiency and equal treatment in prosecutorial practice. Based on the principle of hierarchy, the power of the Republic Public Prosecutor entails issues pertaining to the autonomy of the prosecutor's office as well as the consistent performance of activities entrusted to public prosecutors and deputy public prosecutors. On the one hand, he/she is a public figure and, on the other hand, he/she is a legal expert whose professional authority will guarantee the efficiency of public prosecutors and protection of their professional reputation.